2010
DOI: 10.1186/1743-422x-7-204
|View full text |Cite
|
Sign up to set email alerts
|

Anti-hepatitis B core antigen testing with detection and characterization of occult hepatitis B virus by an in-house nucleic acid testing among blood donors in Behrampur, Ganjam, Orissa in southeastern India: implications for transfusion

Abstract: BackgroundOccult hepatitis B virus (HBV) infection might transmit viremic units into the public blood supply if only hepatitis B surface antigen (HBsAg) testing is used for donor screening. Our aim was to evaluate the prevalence of occult HBV infection among the HBsAg negative/antiHBc positive donations from a highly HIV prevalent region of India.MethodsA total of 729 HBsAg negative donor units were included in this study. Surface gene and precore region were amplified by in house nucleic acid test (NAT) for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
39
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 35 publications
5
39
0
2
Order By: Relevance
“…Occult HBV during the non-replicative phase has been found to be more frequent in areas where genotypes A, D, and E are prevalent rather than genotypes B and C [4,21]. Our report is in accordance with an earlier report [5] from India that revealed HBV/D as the prevalent genotype among OBI cases.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Occult HBV during the non-replicative phase has been found to be more frequent in areas where genotypes A, D, and E are prevalent rather than genotypes B and C [4,21]. Our report is in accordance with an earlier report [5] from India that revealed HBV/D as the prevalent genotype among OBI cases.…”
Section: Discussionsupporting
confidence: 83%
“…The present study revealed OBI in 10.1% of individuals belonging to the Nicobarese tribe. Varying prevalence of anti-HBc, a marker for exposure to HBV infection, has been reported from different parts of India, ranging between 8% and 18% [5]. Prevalence of occult HBV infection was also high among the anti-HBc positive individuals belonging to the vaccinated and non-vaccinated cohorts from the present study; 64.5% (40/62) of antiHBc-positive cases were HBV DNA positive.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…The highest yield was for HBV infection (6/8) [9]. There are a few other reports from India [10][11][12][13][14][15] which also show that the addition of tests to detect nucleic acids (NAT or PCR) increased the yield of donors who are hepatitis B positive. In China and Taiwan, with a high endemicity of hepatitis B, the addition of NAT increased the detection of occult carriers [16,17].…”
mentioning
confidence: 99%